Dual arm compressive spectral imaging in the visible and IR range (2016)
Imaging spectroscopy involves sensing spatial information in a scene across a range of wavelengths in order to acquire a three-dimensional data cube. Spectral images play an important role in science and technology. Some of their applications require image acquisition in both the visible and the infrared ranges in order to detect characteristics that are not noticeable to the bare eye. These can be perceived in lower layers of the scene where the visible radiation does not penetrate. This paper proposes a compressive image acquisition system that reduces the number of optical elements by jointly and compressively acquiring the images in the visible and infrared spectra. It also evaluates whether the quality of the reconstructed images is good enough to consider the optical implementation of the proposed system. Diverse simulations are performed to determine the peak signal to noise ratio (PSNR) of the data cubes as a function of the coded apertures transmittance, the Gaussian noise applied to the measurements and the number of snapshots. The simulations provide PSNR values of up to 33 dB in the reconstructed images.